Journey from Teaching to Learning through Professional Learning Communities Role of School Leadership - Awasthi, Kashyapi (JOURNAL OF INDIAN EDUCATION, 2018)
Teacher Education in the country calls for revolutionary changes. The centrality of teacher and the need for Continuous Professional Development (CPD) has been the focus in many policy documents. However, the cry for quality teachers continues. Developing teacher capacity is critical; it requires a fine blend of pedagogical skills and competencies, knowledge, attitude, positive learning, organisational conditions and culture, and above all, a reflective dialogue leading to lifelong learning and passionate rendering. The author in this paper deliberates on the idea of Continuous Professional Development (CPD), making teachers responsible and aware about their own professional development and developing teachers as reflective practitioners through the formation of Professional Learning Communities (PLC). The paper also shares the role of heads of schools in initiating PLC in school, and amongst schools at the cluster level, thus empowering teachers through academic leadership, gradually moving towards whole school improvement.